Modern view of the pathogenetic mechanisms of the limbic system role in the forming of pain syndromes in pharmacoresistant facial sympathalgia - Лекомцева, Євгенія Володимирівна (Psychiatry, Neurology and Medical Psychology, 2019)
The present work was devoted to pharmacoresistant facial sympathalgia which held one of the frequent places among other neuropatic acute and chronic pain syndromes; they usually characterized by long-term clinical course and severe pain which is resistant to conducted conservative therapy by several pharmaceutical drugs. In this paper the general modern data about the etiopathogenetic mechanisms and the role of limbic system, its other anatomical and physiological parts in the genesis and forming of pain paroxysms in facial sympathalgia were presented. Pharmacoresistant facial sympathalgia differs from the other pain syndromes with more similar and typical localization, the severity of clinical manifestations, the presence of neurological deficit, long-recurrent clinical course, resistance to various treatment methods, both therapeutic and neurosurgical, and different somatic complications. At the autonomic response disturbances, epileptic or paroxysmal focus plays the leading disorganizing role, located mainly in the medial structures of the limbic-reticular complex. It has been established, that the limited convulsive activity in various structures of the limbic-reticular complex is the pathogenesis basis of non-epileptic or painful paroxysms, which does not reach of the formation of morpho-functional epileptic system because of influence of various stabilizing factors. Also it was discussed that in the pathogenetic mechanisms any changes in the functional state of the pain-sensing nociceptive and antinociceptive systems and leading neurotransmitters have played the certain role in pharmacologically resistant facial sympathalgia where glutamate and aspartate are being modulators of the convulsive and neuroplastic brain activity, directly and indirectly participating in the formation of processes of excitation and pain threshold, different neurotoxic processes.